AIR DEFENCE OPERATION DEFENCE IN DEPTH STRATEGY TO PROTECT THE AEROSPACE SOVEREIGNITY OF CROSSRIGHT VIOLATIONS BY FOREIGN MILITARY AIRCRAFT IN 2012-2017 - Zalia, Hadaina; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to explain the reasons of Indonesia for deploying Air Defence Operation (Operasi Pertahanan Udara) Defence In Depth Strategy to safeguard the aerospace sovereignty of cross-rights violations by foreign military aircraft in 2012 to 2017. The escalation of air threats that develop into a violation by foreign military aircraft will threaten the sovereignty of NKRI. Opshanud defence in depth is implemented by the National Air Defence Command (Komando Pertahanan Udara Nasional) which has many functions, one of them is air defence operations function.The study was prepared using the Security Strategy theory by John P. Lovell, the concept of national security, the realist perspective, and state-degree analysis. This research also uses descriptive analysis with qualitative approach. Data collection techniques used were interviews (structural and unstructural) and literature studies.The results of this study indicate that Indonesia deploy aero defence operation defence in depth based on Indonesia?s defence capability. Defence capabilities can be seen from government policy in the field of defence, development of strategic environment, procurement of defence equipment and defence budget. In order to maintain effective and efficient aerospace sovereignty, airspace is divided into several air defence sectors: areal air defence, pointed air defence, and terminal air defence.Keywords: defence, air, violations, security, strategy